KONSEP DASAR EVALUASI BELAJAR DAN PEMBELAJARAN - Siti Sholikhati; Daniel Agus Wibowo (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2026)
Assessment is an effort that can be done to find out what will happen that has been achieved by educators in the learning process. Assessments carried out by educators can be in the form of learning achievement assessments and learning assessments. The activity of controlling the determination of quality and guaranteeing learning for various kinds of learning components in every path and level of learning is a form of accountability for the implementation of education which is an assessment of learning. The test is a number of tasks that must be done or a set of questions that must be answered for students to measure the level of understanding and mastery of the required range of material and according to specific learning objectives. Thus it was concluded that the main measuring tool that is often used in learning assessment besides other measuring tools is the test